Motor learning requires myelination to reduce asynchrony and spontaneity in neural activity. Issue 1 (29th August 2019) - Kato, Daisuke; Wake, Hiroaki; Lee, Philip R.; Tachibana, Yoshihisa; Ono, Riho; Sugio, Shouta; Tsuji, Yukio; Tanaka, Yasuyo H.; Tanaka, Yasuhiro R.; Masamizu, Yoshito; Hira, Riichiro; Moorhouse, Andrew J.; et al.
Abstract: Myelination increases the conduction velocity in long‐range axons and is prerequisite for many brain functions. Impaired myelin regulation or impairment of myelin itself is frequently associated with deficits in learning and cognition in neurological and psychiatric disorders. However, it has not been revealed what perturbation of neural activity induced by myelin impairment causes learning deficits. Here, we measured neural activity in the motor cortex during motor learning in transgenic mice with a subtle impairment of their myelin. This deficit in myelin impaired motor learning, and was accompanied by a decrease in the amplitude of movement‐related activity and an increase in the frequency of spontaneous activity. Thalamocortical axons showed variability in axonal conduction with a large spread in the timing of postsynaptic cortical responses. Repetitive pairing of forelimb movements with optogenetic stimulation of thalamocortical axon terminals restored motor learning. Thus, myelin regulation helps to maintain the synchrony of cortical spike‐time arrivals through long‐range axons, facilitating the propagation of the information required for learning. Our results revealed the pathological neuronal circuit activity with impaired myelin and suggest the possibility that pairing of noninvasive brain stimulation with relevant behaviors may ameliorate cognitive and behavioral abnormalities in diseases with impaired myelination. Main Points: Myelin impairment results in temporal dispersion of axonal conduction in long‐range axons. Low task‐related and high spontaneous activity induced by myelin impairment causes motor learning which is compensated by synchronized optical stimulation